Volleyball: similar game for men and women? Factors characterising successful performance in Olympic Games 2021 regarding genders - Drikos, S.; Fatahi, A.; Molavian, R.; Al-Ryami, S. A. A.; Sotiropoulos, K.; Barzouka, K. (International Journal of Performance Analysis in Sport, 2024)
The goal of this study was to survey the effectiveness of the factors characterising successful performance in volleyball between men and women in games played in the Olympic Games 2021 tournaments. Seventy-six matches (38 matches per gender) were sampled, and data were collected from N = 560 sets (N = 292 for men and N = 268 for women). Principal component analysis was conducted on 15 performance indicators with orthogonal rotation (varimax). The principal component scores saved from the analysis were run in binomial logistic regression (Win/Loss) forced entry regression analysis using a data splitting method on a random selection of 50% of the data (training and test sample). The models produced were then used to predict the probability of winning the set using the same variables for the remaining 50% data. The results provide evidence that between genders there are common important factors which affect the evolution of a set and therefore if improved can increase the probability of winning, however with the same level of improvement, the odds differentiate per gender. These findings and inferences can be used as guidelines for coaches of teams of both genders concerning the skills that require further improvement.